Illness perceptions in Raynaud’s phenomenon: A qualitative study - Mashal Hajar Safi; Paula Smith; Johanna Meyer; Jo Daniels (Health Psychology Open)
Raynaud’s Phenomenon is a condition characterised by vasoconstriction of the extremities and can have a detrimental impact on people’s lives. The treatment options for patients currently offered through healthcare services, e.g., in the United Kingdom (UK), are insufficient. This study provides a theoretical basis for future interventions by presenting insights into experiences of living with Raynaud’s. Using an inductive-deductive approach, our thematic analysis of 19 semi-structured interviews with people living with Raynaud’s in the UK was informed by the common-sense model of self-regulation. Three interrelated themes were generated to capture the illness experiences of people with Raynaud’s: 1) Illness representations, 2) Coping response, and 3) Advice and guidance. Together, these themes provide insight into illness perceptions, coping styles and factors that may contribute to adherence to self-management. The findings suggest that a stepped care approach to managing Raynaud’s may be beneficial.